Patient-derived acute myeloid leukemia (AML) bone marrow cells display distinct intracellular kinase phosphorylation patterns - Keith Shults (Cancer Management and Research, 2009)
Keith Shults1, Leanne Flye1, Lisa Green2, Thomas Daly2, Jason R Manro2, Michael Lahn21Esoterix, Brentwood, TN, USA; 2Eli Lilly and Company, Lilly Research Laboratories, Indianapolis, IN, USAAbstract: Multiparametric analyses of phospho-protein activation in patients with acute myeloid leukemia (AML) offers a quantitative measure to monitor the activity of novel intracellular kinase (IK) inhibitors. As recent clinical investigation with FMS-like tyrosine-3 inhibitors demonstrated, targeting IK with selective inhibitors can have a modest clinical benefit. Because multiple IKs are active in patients with AML, multikinase inhibitors may provide the necessary inhibition profile to achieve a more sustained clinical benefit. We here describe a method of assessing the activation of several IKs by flow cytometry. In 40 different samples of patients with AML we observed hyper-activated phospho-proteins at baseline, which is modestly increased by adding stem cell factor to AML cells. Finally, AML cells had a significantly different phospho-protein profile compared with cells of the lymphocyte gate. In conclusion, our method offers a way to determine the activation status of multiple kinases in AML and hence is a reliable assay to evaluate the pharmacodynamic activity of novel multikinase inhibitors.Keywords: leukemia, AML, bone marrow, flow cytometry